THE EFFECT OF DEMONSTRATION METHOD EDUCATION ON ADOLESCE SELF-AWARENESS AND HYGIENE BEHAVIOR DURING MENSTRUATION AT THE HAFSHAWATY ISLAMIC BOARDING SCHOOL ZAINUL HASAN PROBOLINGGO - Siti Fatimah Tus Zahroh; Achmad Kusyairi; Iin Aini Isnawati (Media Inovasi Pendidikan dan Publikasi, 2023)
Self-awareness is a state of awareness in evaluating oneself so that one is able to control oneself. Genetalia hygiene behavior is an effort to maintain cleanliness and prevent disease to improve health status. This study aims to determine whether there is an effect of demonstration education on self-awareness and genital hygiene behavior during menstruation. Pre-post design with observation and questionnaires makes up the research methodology. Saturated sampling, with inclusion and exclusion criteria, is utilized to collect data from 42 respondents from all pupils. The results of this study obtained self-awareness and genital hygiene behavior at the time of pre-post. Showing the results of self-awareness in the pretest the majority of the less category as many as 33 respondents (78.5%). In the post-test data, the majority of the medium category were 31 respondents (73.8%). Meanwhile, the majority of hygiene behavior in the pretest category was sufficient as many as 23 respondents (54.8%). The majority of post-test data were in sufficient category as many as 35 respondents (83.3%). Wilcoxon test results obtained p-value: 0.000 <0.05. This shows that there is an effect of demonstration education on adolescent self-awareness and genital hygiene behavior during menstruation at Female Hafshawaty Islamic Boarding School Zainul Hasan Probolinggo. It is anticipated that adolescents will become more self-aware and practice good genital hygiene. For future investigations, demonstrations might be created to assess genital hygiene practices during menstruation.